Bee pollination: an environmental education proposal through a pedagogical game - Horsth, Lucinea Carolina; de Azevedo Bicalho, Thais; Terra Soares, Jessica; Holanda Righetti de Abreu, Vanessa (Guará Journal, 2025)
The indiscriminate use of pesticides negatively affects the survival and reproduction of native bees. This paper describes an environmental education proposal implemented through a set of educational activities, including the educational game "Poliniza – o jogo das flores" (Pollinize – the flower game), developed with low-cost materials and implemented in informal learning environments. This environmental education initiative engaged different audiences during an event at a brazilian enviromental reserve called “ARIE Laerth Paiva Gama”, sited at Alegre city, Espírito Santo state, Brazil, promoting engagement and learning about pollination. Among the most relevant outcome patterns, we highlight that children from neighboring gardens returned with family members and shared explanations about the pollination process; private school students related the content to plants grown at home; and local farmers sought technical information on bee conservation. These reports demonstrate the activity's potential to integrate popular and scientific knowledge and promote interest and engagement in biodiversity conservation issues.
Keywords: Native bees; Biodiversity; Conservation; Teaching